Hubungan Konseling Menyusui Dengan Sikap Ibu Dalam Pemberian Asi Eksklusif Di Wilayah Kerja Puskesmas Tawaeli - Tempali, Sri Restu; Rafika, Rafika; Muliani, Muliani; Tondong, Henrietta Imelda (Poltekkes Kemenkes Palu, 2018)
Exclusive breastfeeding is the most appropriate food for babies aged 0-6 months for brain development and infant intelligence as well as to improve the baby's immune system or immunity from disease attacks. The coverage of exclusive breastfeeding is influenced by many factors, one of which is the very limited number of ASI counselors. The purpose of this study is to know the relationship of breastfeeding counseling with mother's attitude in exclusive breastfeeding in Tawaeli Health Center work area. This research includes descriptive correlation type with cross sectional approach. The design of this study was used to analyze the correlative relationship between breastfeeding counseling and the mother's attitude in exclusive breastfeeding. The location of this research is the work area of Puskesmas Taweli in Palu City and implemented on July to August 2015. The sample of this research is all mothers who have babies aged 0-6 months in work area of Puskesmas Taweli in Palu City. Sampling was done by using consecutive sampling, with total sample of 73 people. The results showed no significant relationship between breastfeeding counseling and mother's attitude in exclusive breastfeeding in Tawaeli Health Center Working Area. This can be proved by statistical analysis with X2value <X2table (0,292 <92,808) at 95% CI and ρ-value = 0,589> α (0,05). Based on the result of the research, it can be concluded that there is no relationship of breastfeeding counseling with mother attitude about exclusive breast feeding in Tawaeli Public Health Working Area.Keywords: 0-6 months old baby, Mother’s attitude, Counseling